The role of accounting reform in achieving the requirements of optimum usage of the financial accounting system according to the mechanisms proposed for modernization - Hadjadj , Zineb; Announ , Fouad (Journal of Research in Finance and Accounting, 2021)
This study clarifies the accounting reform applied in Algeria through the implementation and usage of the financial accounting system, In an attempt to give the international dimension to the accounting practices of the Maghreb countries, then the study tries to evaluate the usage of the accounting system in accordance with the accounting and economic environment requirements, in order to propose a systematic mechanism to ensure the modernization of the accounting system. The study concluded that the accounting reform must continue to be applied periodically and not gradually, in order to ensure the continuity of the compatibility between local accounting environment and international accounting framework. Consequently, the study suggests the necessity of establishing a specialized committee to undertake the calibration tasks at the local level to develop the accounting profession and to give it an international dimension as well .Also, The factors that enhance the achievement of the goals of accounting reform are to benefit from the prevailing accounting practices in different countries and to understand the environmental variables to achieve the effectiveness of compatibility with international standards, and to adapt the accounting system according to the Algerian economic environment, with taking into account the parallel development of both of them.